HUBUNGAN PANJANG DAN KEKUATAN OTOT TUNGKAI BAWAH TERHADAP POWER DALAM PERMAINAN BOLA VOLI PADA CLUB UNDANA VOLLEY BALL - Anggi Riliana Abanat; Lukas Maria Boleng; Michael Johannes Hadiwijaya Louk (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2021)
Addressed Research Questions: (1) what is the correlation between the length of the lower limb and the power in the volleyball game at Undana volleyball club?; (2) What is the correlation between the lower limb muscle strength and the power in a volleyball game at Undana volleyball club?; and (3) What is the correlation between the length and the muscle strength of the lower limb to the power in the volleyball game at Undana volleyball club?This study aimed to investigate the relations of: (1) lower limb length and the power in a volleyball game at the Undana volleyball club; (2) lower limb muscle strength and the power in a volleyball game at the Undana volleyball club; and (3) the length and muscle strength of the lower limb and the power in a volleyball game at the Undana volleyball club.The study was conducted at the P2AT volleyball court in Kupang with a total of 16 female volleyball athletes from the Undana Volleyball Club. The researcher collected the data by measuring the length of lower limbs, performing lower limb muscle strength tests on the athletes due to the differences in each athlete. The result of the measurements would be compiled and analyzed to determine the conclusion. The correlation method was employed as the research method to distinguish the relationship between one variable to another.The findings showed that the test and the measurements yield the calculated r-value of lower limb length and leg muscle strength to power at a significant level of 5% and df 15 was 0.421 > r table 0.468 which meant that the length and strength of the lower limb muscles have a significant correlation to power in volleyball games at the Undana volleyball club.In conclusion, there is a significant correlation between the length and the strength of the lower limb to the power in a volleyball game at the Undana volleyball club.